Epithelial Heat Shock Proteins Mediate the Protective Effects of Limosilactobacillus reuteri in Dextran Sulfate Sodium-Induced Colitis - Liu, Hao-Yu; Gu, Fang; Zhu, Cuipeng; Yuan, Long; Zhu, Chuyang; Zhu, Miaonan; Yao, Jiacheng; Hu, Ping; Zhang, Yunzeng; Dicksved, Johan; Bao, Wenbin; Cai, Demin (Frontiers in Immunology, 2022)
Defects in gut barrier function are implicated in gastrointestinal (GI) disorders like inflammatory bowel disease (IBD), as well as in systemic inflammation. With the increasing incidence of IBD worldwide, more attention should be paid to dietary interventions and therapeutics with the potential to boost the natural defense mechanisms of gut epithelial cells. The current study aimed to investigate the protective effects of Limosilactobacillus reuteri ATCC PTA 4659 in a colitis mouse model and delineate the mechanisms behind it. Wild-type mice were allocated to the control group; or given 3% of dextran sulfate sodium (DSS) in drinking water for seven days to induce colitis; or administered L. reuteri for seven days as pre-treatment; or for 14 days starting seven days before subjecting to the DSS. Peroral treatment of L. reuteri improved colitis severity clinically and morphologically, and reduced the colonic levels of TNF-α (Tnf), Il1β, and Ifng, the crucial pro-inflammatory cytokines in colitis onset. It also prevented the CD11b+Ly6G+ neutrophil recruitment, and the skewed immune responses in mesenteric lymph nodes (MLNs) of CD11b+CD11c+ dendritic cells (DCs) expansion and Foxp3+CD4+ T cells reduction. Using 16S rRNA gene amplicon sequencing and RT-qPCR, we demonstrated a colitis-driven bacterial translocation to MLNs and gut microbiota dysbiosis which were in part counterbalanced by L. reuteri-treatment. Moreover, the expression of barrier preserving tight junction (TJ) proteins and cytoprotective heat shock protein (HSP) 70 and HSP25 were reduced by colitis, but boosted by L. reuteri-treatment. A shift in expression pattern was also observed with HSP70 in response to the pre-treatment, and with HSP25 in response to L. reuteri-DSS, respectively. In addition, the changes of HSPs were found to be correlated to bacterial load, and epithelial cell proliferation. In conclusion, our results demonstrate that the human-derived L. reuteri strain 4659 confers protection in experimental colitis in young mice. While intestinal HSPs may mediate the probiotic effects by providing a supportive protein-protein network for the epithelium in health and colitis.